Crystal growth mechanisms of the (010) face of alpha-lactose monohydrate crystals - Dincer, Tuna; Ogden, Mark; Parkinson, Gordon (Elsevier, 2009)
The growth rates of the (010) face of a-lactose monohydrate crystals were measured at 30, 40 and 50 1C in the relative supersaturation range 0.55?2.33 in aqueous solutions. The mechanisms of growth were investigated. Spiral growth was found to be the mechanism of growth up to a critical relativesupersaturation (s-1)crit=1.9 at 30 1C. Above the critical relative supersaturation, the crystal growthmechanisms were predicted to change. All growth models fit equally well to the growth rates. No twodimensional nucleation was observed above critical supersaturation by AFM. On the other handincreased step height and roughness on the edges of steps were observed. It was concluded that thegrowth mechanism of the (010) face of a-lactose monohydrate crystal is spiral growth. A parabolicrelationship was obtained below critical supersaturation followed by a linear relationship with relativesupersaturation.